Public Options and Altruistic Firms - Antitrust Targets or Tools? The Welfare Impact of a Mixed Oligopoly With Managerial Firms - Johan Willner (Aboa Centre for Economics (ACE), 2010)
I analyse the welfare impact of a mixed market with a public or private firm with some degree of altruism, in the presence of an agency problem. Contrary to some earlier findings, the total surplus turns out to be increasing in the degree of altruism. This impact is stronger than if there is no agency problem, despite more stringent conditions for the market to remain mixed. The altruistic firm is more cost-efficient, and viable if the market can remain mixed. A competition policy that encourages entry may increase welfare, but its scope is reduced by higher altruism.
Keywords: L32; L33; L44; H42; 330; non-profit maximising firms; public firms; mixed oligopoly; competition policy